Development of Canva-Based Electronic Student Worksheets (E-LKPD) for Elementary School Students: A Systematic Literature Review - Ira Zakiyah (Sains Global Institut, Indonesia, 2026)
Education in the digital era demands learning media innovations that are not only informative but also interactive and capable of stimulating students' active engagement. At the elementary school level, the use of conventional Student Worksheets (LKPD) often faces various challenges, ranging from visual limitations and monotonous displays to students' low interest in reading and learning. The rapid development of information and communication technology has encouraged educators to transform printed LKPD into Electronic Student Worksheets (e-LKPD), which offer multimedia integration and more interactive learning experiences. This study aims to systematically review research findings related to the development of Canva-based e-LKPD in elementary schools. Specifically, this study seeks to identify the dominant development procedures, determine the validity level of Canva-based e-LKPD according to expert evaluations, and analyze its effectiveness in improving elementary school students' learning outcomes. The study employed a Systematic Literature Review (SLR) method by examining relevant research articles published between 2020 and 2026. The findings indicate that the ADDIE and 4D models are the most frequently used development models. The validity level of Canva-based e-LKPD consistently falls within the